2012
DOI: 10.1108/17468771211207376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of international collaboration and knowledge moderation on China's nanotechnology research impacts

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:305060 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…In spite of the rich volume of results in the literature, they are in disagreement (Tang & Shapira, 2012). Since the seminar work of Katz and Martin (1997), the amount of evidence supporting the positive correlation between collaboration and research performance has been accumulating.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In spite of the rich volume of results in the literature, they are in disagreement (Tang & Shapira, 2012). Since the seminar work of Katz and Martin (1997), the amount of evidence supporting the positive correlation between collaboration and research performance has been accumulating.…”
Section: Introductionmentioning
confidence: 90%
“…A CKM is a researcher who bridges two different scientific communities of China and other countries via intensive collaboration (Tang & Shapira, 2012). In this particular research, the notion is confined to the US and China collaboration context.…”
Section: Selection Of Chinese Knowledge Moderatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This conjecture is partially supported by our data. When grouping Hong Kong's SSCI publications by Chinese versus non-Chinese surnames based on the thesauri developed by Tang and Shapira (2012), we found that about 86% involve at least one researcher with a Chinese family name over the examined period. When excluding foreign institutions, the figure remains at the same rate.…”
Section: Key Actors At Organizational Levelmentioning
confidence: 98%